Government guarantees and financial stability - Franklin Allen; Elena Carletti; Itay Goldstein; Agnese Leonello (European Central Bank (ECB), 2017)
Banks are intrinsically fragile because of their role as liquidity providers. This results in under-provision of liquidity. We analyze the effect of government guarantees on the interconnection between banks' liquidity creation and likelihood of runs in a model of global games, where banks.and depositors' behavior are endogenous and affected by the amount and form of guarantee. The main insight of our analysis is that guarantees are welfare improving because they induce banks to improve liquidity provision although in a way that sometimes increases the likelihood of runs or creates distortions in banks' behavior.
Keywords: G21; G28; 330; panic runs; fundamental runs; government guarantees; bank moral hazard